Standards in breast surgery – Breast Units – future and necessity - Madej-Czerwonka, Barbara Teresa (Contemporary Oncology/Współczesna Onkologia, 2014)
Breast cancer is the most common type of malignant neoplasm affecting women. In Poland there are nearly 15 500 new cases of the disease and over 5200 deaths due to it observed annually. As it was necessary to provide those suffering from breast cancer with combined highly specialist treatment, it was required that separate units specialising in breast surgery be established. In Europe they are referred to as Breast Units. The idea of forming such separate and fully profiled centres specialising in breast diseases, which was developed in 1998 by EORTC, EUSOMA as well as Europa Donna, gave foundations for the organisation of such centres. The situation of Breast Units in other European countries is different. Poland has failed so far to organise an effective system of Breast Units. Leading Polish authorities underline that formation of multi-disciplinary Breast Units is the organisational priority for the year 2013.